Peran Pelajaran Perpustakaan dalam Pengenalan Kepustakaan: Studi Kasus SD Madania - Ghassani, Felisha (UI Scholars Hub, 2018)
This article focuses on library learning activities at Madania Primary School. This journal also explains about the activities carried out by the National Library of Indonesia in introducing libraries. The purpose of this journal is to find out the library learning activities at Madania Primary School and the obstacles they face. This research was conducted with qualitative methods. Data collection is done by interviewing, observing and documents studying. The conclusion of this study is that Madania Primary School library does not provide classroom supporting education in general. Moreover, the library provides library education so students are encouraged to be independent in learning, explore information, and maintain collections. Library learning is not in the form of learning to read or help class material in class. The lessons provided are knowledge about libraries covering four main topics, namely library values, library skills, literature skills, and research skills. The obstacle faced by the library staff is the difficulty of class management. Library staff who does not have a background in library science are also an obstacle in teaching.